Utilization of Digital Marketing and Financial Management to Improve Business Performance in KSC Cafe - Sari, Eka Purnama; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The large number of cafes in Jogja means the owners have to think creatively to create something different to win the competition. Owners need to manage their business well, especially in the areas of digital marketing and financial management. This internship activity introduces companies to utilizing digital marketing through creating Instagram Reels and Tiktok marketing content, creating customer databases and financial management. This internship activity aims to improve KSC's business performance. The result was developing the skills of KSC employees in creating interesting marketing content through Reels and Tiktok, successfully adding new marketing channels through the Tiktok platform, using creator services with a free budget, having a customer database, knowing customer satisfaction levels and effective financial records.